First you must combine like terms, the two terms I this expression are x, and xy. So by adding -2xy to -2xy you get -4xy. Next you must add 3x to 3x. This gives you the simplified expression -4xy+6x. Hope this helps
Hello,
Answer:
The last graph (2;3)
Step-by-step explanation:
2x + 3y = 12
2x – 3y = 0
2x + 3y = 12
2x = 3y
3y + 3y = 12 ⇔ 6y = 12 ⇔ y = 12/6 = 2
2x + 3 × 2 = 12 ⇔ 2x + 6 = 12 ⇔ 2x = 6 ⇔ x = 6/2 = 3
X/4 = r3 or 3/4
x/3 = r2 or 2/3
x/5 = r3 or 3/5
we know x is not divisible by 4 3 or 5 and is less than 30.
we know the value ends in 3 or 8 from x/5 = r3
we know the value is greater than 3 from r3
so far we got 13 and 23
13 is eliminated from x/4 = r3 because it is r1 not r3
so the answer is 23